Special Educational Needs and Disabilities reforms 2014: SENCos' perspectives of the first six months. (March 2017) - Curran, Helen; Mortimore, Tilly; Riddell, Richard
Abstract : The Special Educational Needs and Disabilities (SEND) reforms have been reported as the most significant reforms of their kind for over 30 years. Through the Children and Families Act2014 the Government is seeking to effect cultural change regarding SEND. The SENCo is responsible for the operational and strategic aspects related to SEND provision within the school and as such could be considered a key implementer of the reforms. This article forms part of a PhD research project which is developing research within the area of SEND policy reform, through exploring and analysing the in‐depth experience of the SENCo as a policy implementer during the first academic year post‐reform. This article discusses the emerging themes from one of the wider data sets which sought to gather the views of SENCos six months after the introduction of SEND reforms and the SEND Code of Practice.